Efficacy and Safety of Intravenous Ferric Carboxymaltose In Patients with Chronic Heart Failure and Associated Iron Deficiency: Insights from a Tertiary Care Research Institute In India - Jain, Rajendra Kumar; Azam, Mohammed Sadiq; Swami, Onkar C; Jain, Neha (Cardiology and Cardiovascular Medicine, 2023)
Objectives: To assess the efficiency and safety on Intravenous Ferric Carboxymaltose (IV FCM) in correcting Iron Deficiency (ID) in patients with chronic heart failure (CHF). Methods: A Prospective, Observational single center study was performed in a tertiary care teaching institute in India for 12 weeks. Inclusion criteria was patients of both genders, age > 18 years, stable and ambulatory with CHF and associated ID (Absolute & Functional) and belonging to New York Heart Association (NYHA) Class II- III. Patients who didn’t meet the inclusion criteria were excluded from the study. Assessment of NYHA Class, Ejection Fraction (EF) and Iron indices [S. Haemoglobin (Hb), S. Iron, S. Ferritin, Total Iron Binding Capacity (TIBC) and Transferrin Saturation (TSAT)] was done at baseline and 12 weeks after giving IV FCM. A p value of < 0.05 was considered significant. Results: Total 31 patients completed the study (14 males and 17 females). The mean age of patients was 60.81 years and mean Serum Ferritin level was 13.08 μg/l. Majority had HFpEF (61.3%) followed by HFrEF (32.3 %). Upon administering IV FCM, 100% improvement was seen in NYHA class while mean EF increased by 2.8% (p=0.001). A statistically significant improvement was also seen in Hb and Iron indices. No adverse event was reported. Conclusion: Patients treated with IV FCM showed improvement in EF, NYHA class and Iron indices over 12-weeks and had no adverse reactions. IV FCM effectively and safely corrects ID in patients with CHF.